2001
DOI: 10.1530/rep.0.1220745
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analyses of semen and endocrine characteristics of free-living versus captive jaguars (Panthera onca)

Abstract: Semen and blood samples were obtained from free-living (n = 6) and captive (n = 8) jaguars (Panthera onca) to compare reproductive characteristics between the two populations. Semen samples were analysed for volume (ml), percentage of motile spermatozoa, rate of forward progression (0-5), concentration (10(6) ml(-1)), total sperm count (10(6)) and sperm morphology. Serum testosterone concentration was determined by radioimmunoassay. Although ejaculate volume was greater in captive jaguars (n = 47 samples) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
2
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 15 publications
3
42
2
9
Order By: Relevance
“…The data on semen characteristics may be useful to establish normative reproductive values in this species. Electroejaculation would be a safe and reliable method for collecting semen from free-ranging Japanese black bears, as has been recognized in other species [5,10,12,15,18,21,35]. Semen samples obtained under such conditions could subsequently be used in genetic analyses and tests of sexual maturity and competence.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The data on semen characteristics may be useful to establish normative reproductive values in this species. Electroejaculation would be a safe and reliable method for collecting semen from free-ranging Japanese black bears, as has been recognized in other species [5,10,12,15,18,21,35]. Semen samples obtained under such conditions could subsequently be used in genetic analyses and tests of sexual maturity and competence.…”
Section: Discussionmentioning
confidence: 98%
“…There are several reports on semen collection by electroejaculation in other free-ranging mammalian species, such as African elephant [10], jaguar [21], seal [18], Eastern grey kangaroo [15] and koala [35], while fewer reports about cryopreservation of erectroejaculates from free-ranging mammals such as African elephant [12], impala, wart hog, elephant and lion [5]. The inherent difficulties in collecting physiological data from free-ranging bears are reflected in the small number of samples, representing the sparse number of we had capture opportunities over the 3-year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electroejaculation was performed as previously described by Morato et al (16). Briefly, a rectal probe (2.6 cm in diameter and 29 cm long) and a portable batteryoperated electrostimulator (AC, 60 Hz current; Eletrovet Electronic Equipment, São Paulo, SP, Brazil) were used to deliver an electroejaculation stimulus sequence consisting of a total of 80 stimuli applied in a series of 30, 30 and 20 stimuli.…”
mentioning
confidence: 99%
“…Moreover, some researchers have reported successful semen collection from wild felids by using electroejaculation, such as tigers (Panthera tigris- Donoghue et al, 1992), snow leopards (Panthera uncia- Roth et al, 1994), Indian leopards (Panthera pardus- Jayaprakash et al, 2001), caracals (Caracal caracal- Pope et al, 2001), jaguars (Panthera onca- Morato et al, 2001;Silva et al, 2003), ocelots (Leopardus pardalis- Queiroz et al, 2002), margays (L. wiedii) and tigrinas (L. tigrinus- Morais et al, 2002). Graham et al (1978) reported the use of electroejaculation to collect semen from nondomestic felids.…”
Section: Electroejaculationmentioning
confidence: 99%